Loretta O’Donnell, Nazarbayev University, Kazakhstan - Quinn, Callan (Pie Chat, 2019)
Kazakhstan, like its Russian neighbour to the north, is currently on a mission to revamp its educational system and plug itself into the landscape of international higher ed. The PIE spoke with Loretta O’Donnell, vice provost of Academic Affairs at Nazarbayev University in the capital Nur-Sultan (formerly known as Astana), about how the industry is being swept up in the Central Asian nation’s push for reform and internationalisation...
Keywords: education; Kazakhstan; Nazarbayev University; Loretta O'Donell